Parental Involvement in School Program at Bintang Juara Early Childhood Education (ECE) - Juwita, Tusifa; Suminar, Tri; Handayani, Sri Sularti Dewanti (Journal of Primary Education)
This research aims to study and analyze parents’ involvement at school in the Early Childhood Education program. This research was conducted in Bintang Juara Early Childhood Education. The data were obtained from the principal, class teachers, parents, and related documents. This research applied a qualitative approach case study design. The result showed that first, there are various forms of parental involvement in Early Childhood Education. Second, there are positive results of parents’ involvement towards children, parents, teachers, and school programs, such as facilitating the access of school marketing, enhancing children learning, increasing parents’ learning motivation, supporting program achievement, becoming knowledge and information sharing a place, tightening the family relationship. Third, there are supporting and inhibiting factors affecting parents’ involvement, namely internal factor (readiness, parents’ personality, school, and children) and external factor (social, politic, and economic). Fourth, there are effective efforts to support parental involvement in Early Childhood Education programs such as effective and proactive communication, providing suitable time, and creating a friendly environment. These results become the reflection and evaluation subject to school concerning the progress of implemented programs. For parents, they gain a comprehensive image of school partnership parenting education to attain optimum child’s development.